ANALISIS KUAT TEKAN BATU BATA DENGAN ONGGOK SEBAGAI BAHAN PENGGANTI SEKAM PADI - Ngudi Hari Crista; Agus Muldiyanto (Teknika, 2018)
The most widely used material as a house wall is red brick, which is relatively cheap and safe to weather compared to other materials. Red bricks are usually in the manufacturing process by traditional means and fabrication. In general red bricks require additional materials of rice husk in the process of making. Much of the "starchy" waste material widely found in Klaten that is not currently utilized, is expected to be used instead of rice husk which is one of the red brick material mixtures.This research will be conducted brick test with mechanical behavior test which includes density test, water absorption test and compressive strength test with red brick made from rice husk mixture as comparison with analysis result of mixture of starch onggok waste. The result of this research is compressive strength of brick with mixture of rice husk larger and has a small water absorption compared with compressive strength of brick with mixture of onggok.